Perilaku agresi pada remaja anggota pencak silat: Menguji peranan konformitas teman sebaya pada perilaku agresi (SUKMA : Jurnal Penelitian Psikologi, 2022)
Abstract Attacking or injuring behavior both physically and verbally often occurs in adolescents, they tend to be unstable so that they can injure other people who have different opinions or views. The purpose of this study was to find out whether there is a positive relationship between conformity and aggressive behavior in young members of Martial Arts. The population in this study were teenagers who were members of the Setia Hati, Kera Sakti, Pagar Nusa, and others martial arts communities. The sampling technique in this study used an incidental sampling technique. The number of samples in this study were 168 young members of pencak silat. The research design uses quantitative research with conformity scale measuring instruments and aggressive behavior scales. In data analysis using the Pearson product moment parametric correlation technique with the IBM SPSS 26 for windows program. The results obtained were rxy 0.266 with a significance value of p=0.000, where p<0.05. This means that the hypothesis which states that there is a relationship between conformity and aggressive behavior in young members of Martial Arts is accepted. Keywords: Aggressive Behavior, Conformity, Teen, Martial Arts Abstrak Perilaku menyerang atau melukai baik secara fisik mapun verbal sering terjadi diusia remaja, mereka cenderung labil sehingga dapat melukai orang lain yang berbeda pendapat atau pandangan. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada hubungan positif antara konformitas dengan perilaku agresi pada remaja anggota pencak silat. Populasi dalam penelitian ini adalah remaja yang tergabung dalam komunitas pencak silat Setia Hati, Kera Sakti, Pagar Nusa, dan lain-lain. Teknik pengambilan sampel pada penelitian ini menggunakan teknik insidentil sampling. Jumlah sampel pada penelitian ini sebanyak 168 remaja anggota pencak silat. Desain penelitian menggunakan penelitian kuantitatif dengan alat ukur skala konformitas dan skala perilaku agresi. Pada analisis data menggunakan teknik korelasi parametric product moment pearson dengan program IBM SPSS 26 for windows. Hasil yang diperoleh adalah sebesar rxy 0,266 dengan nilai signifikansi p=0,000, dimana p<0,05. Artinya hipotesis yang menyatakan hubungan adakah hubungan antara konformitas dengan perilaku agresi pada remaja anggota pencak silat diterima. Kata kunci: Perilaku Agresi, Konformitas, Remaja, Pencak SIlat